THE CALLA-BASED ELENA MODEL FOR LINGUISTICS: DOES IT WORK? - Syafri, Frimadhona; Rafli, Zainal (IJLECR (International Journal of Language Education and Cultural Review), 2019)
This paper is aimed to describe the implementation of the CALLA-based ELENA model for introduction to linguistics course in the English Department of Universitas Negeri Semarang (UNNES). The research was conducted through descriptive analysis. The analysis of data is the impact of the implementation of the model for the Introduction to linguistics course. Data of the study were collected through observation, questionnaires, and tests. The result of the study shows that using the model can provide the learners' comprehension in learning linguistics concepts. Further, that model has emerged as one of the alternative modes of instruction delivery in the concept of linguistics. This research finding can be used to review current online learning model trends and to explore potential research directions.